1999
DOI: 10.1038/sj.bmt.1701601
|View full text |Cite
|
Sign up to set email alerts
|

Primitive hematopoietic progenitors within mobilized blood are spared by uncontrolled rate freezing

Abstract: Summary:Uncontrolled-rate freezing techniques represent an attractive alternative to controlled-rate cryopreservation procedures which are time-consuming and require high-level technical expertise. In this study, we report our experience using uncontrolled-rate cryopreservation and mechanical freezer storage at −140؇C. /l white blood cells and 50 ؋ 10 9 /l platelets were 9 and 13, respectively. In conclusion, the procedure described here is characterized by short execution time, allows a substantial recovery o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 26 publications
1
35
0
3
Order By: Relevance
“…Other studies have also shown a decrease in CFU-GM or engraftment with long-term storage but are less applicable because of the use of less extreme freezing temperatures 17 or the use of animal models 18 and studies that report no decrease in SCP markers have been limited by relatively short median storage times. [9][10][11][12]19 In this study, recovery of SCP, TNC, cell viability and total CD34 þ cell count decreased as storage time, up to 19 years, increased. No previous study has analysed stem cells stored for this long and no previous study, using PB or BM stem cells, has directly compared individual samples results from the time of original harvest with the current time post long-term storage.…”
Section: Discussionmentioning
confidence: 97%
“…Other studies have also shown a decrease in CFU-GM or engraftment with long-term storage but are less applicable because of the use of less extreme freezing temperatures 17 or the use of animal models 18 and studies that report no decrease in SCP markers have been limited by relatively short median storage times. [9][10][11][12]19 In this study, recovery of SCP, TNC, cell viability and total CD34 þ cell count decreased as storage time, up to 19 years, increased. No previous study has analysed stem cells stored for this long and no previous study, using PB or BM stem cells, has directly compared individual samples results from the time of original harvest with the current time post long-term storage.…”
Section: Discussionmentioning
confidence: 97%
“…Specifically, fast cooling forms intracellular ice crystals, which results in cell destruction and slow cooling forms ice crystals in the extracellular space, with consequent cellular dehydration. Selection of a cryoprotectant, as well as a suitable freezing rate serves to protect cells from these adverse effects (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, this technique requires sophisticated, costly equipment and a certain personal expertise, which are not available at every center (Almici et al, 2003;Perez-Oteyza et al, 1998). Several single armed studies have reported excellent viability and hematopoietic recovery rates with uncontrolled freezing procedures in bone marrow (Clark, Pati, & D. McCarthy, 1991;Stiff, Murgo, Zaroulis, DeRisi, & Clarkson, 1983) and peripheral blood progenitor specimens (Almici et al, 2003;Cilloni et al, 1999;Halle et al, 2001). Few studies directly compared outcomes of controlled rate to uncontrolled rate freezing processes.…”
Section: Alternatives To Standard Dmsomentioning
confidence: 99%
“…Temperatures range from -196°C to -80°Celsius (Aird, Labopin, Gorin, & Antin, 1992;Cilloni et al, 1999;Galmés et al, 1999;Halle et al, 2001;Rubinstein et al, 1995;Son, Heo, Park, H. H. Kim, & K. S. Lee, 2010;Valeri & Pivacek, 1996). The initially used storage temperatures of -196°C, reflecting the liquid phase nitrogen storage, have largely been replaced by temperatures of -156°C to -135°C, reflecting the vapor phase storage (Berz, McCormack, Winer, Colvin, & Peter J Quesenberry, 2007) in BM-, PB-as well as umbilical cord derived stem cells(Aird, Labopin, Gorin, & Antin, 1992;Cilloni et al, 1999;Galmés et al, 1999;Halle et al, 2001;Rubinstein et al, 1995; Son, Heo, Park, H. H. Kim, & K. S. Valeri & Pivacek, 1996). This shift in culture was mainly induced by the observation that infectious pathogens can survive and be propagated in the liquid nitrogen phase (Bielanski & Vajta, 2009).…”
Section: Storage Temperaturementioning
confidence: 99%